Troubling the Discursive Moment: Using Black Texts for Activating Dialogue. Issue 165 (27th March 2020) - Gnanadass, Edith; Merriweather, Lisa R.
Abstract: In this article, the authors challenge the ongoing dehumanization of people of color by arguing for the use of Black texts as core readings in courses on adult learning rather than as add‐ons or "special topics."